H∞ filtering for discrete-time switched fuzzy systems with randomly occurring time-varying delay and packet dropouts - Zhang, Meng; Shi, Peng; Liu, Zhitao; Ma, Longhua; Su, Hongye (Signal processing, 2018)
•H∞ filtering problem for a class of discrete-time switched fuzzy systems with randomly occurring time-varying delay and packet dropouts is investigated in the paper.•The stochastic time-varying delay and packet dropouts phenomenon are assumed to occur in a random way but satisfy the well-known Bernoulli binary distribution, meanwhile, all the stochastic variables under consideration are mutually independent.•A novel delay-dependent piecewise Lyapunov function is introduced, and sufficient conditions are established in the form of linear matrix inequalities, which ensure the filtering error system is exponentially stable with prescribed H∞ performance. In this paper, we investigate H∞ filtering problem for a class of discrete-time switched fuzzy systems with randomly occurring time-varying delay and packet dropouts. The fuzzy plant incorporates features of switched systems and Takagi–Sugeno (T-S) fuzzy systems simultaneously. The stochastic time-varying delay and packet dropouts phenomenon are assumed to occur in a random way but satisfy the well-known Bernoulli binary distribution, meanwhile, all the stochastic variables under consideration are mutually independent. By introducing a novel delay-dependent piecewise Lyapunov function, sufficient conditions are established in the form of linear matrix inequalities, which ensure the filtering error system is exponentially stable with prescribed H∞ performance. Finally, an illustrative example is exploited to verify the effectiveness of the proposed approaches.